Comparison between Ischemic Stroke Patients <50 Years and ≥50 Years Admitted to a Single Centre: The Bergen Stroke Study. (2nd January 2011) - Fromm, Annette; Waje-Andreassen, Ulrike; Thomassen, Lars; Naess, Halvor
Abstract : Introduction . Young adults are likely to differ from old patients concerning cerebral infarction. Methods . We compared characteristics of patients aged under and above 50 years, admitted to the Department of Neurology with cerebral infarction between 2006 and 2009, based on prospective registration. Investigation followed one common protocol for both groups. Results and Discussion . One hundred patients (8.2%) were <50 years old, and the proportion of males was higher in this group (72% versus 55.8%, P = .002 ). Young stroke patients are more often current smokers (44.1% versus 23.6%, P < .001 ). Common causes for stroke in the young were cervical artery dissection (18% versus 0.6%, P < .001 ) and cardiac embolism due to disorders other than atrial arrhythmias (18% versus 5.5%, P < .001 ). Among the old, atrial fibrillation and flutter dominated (29.1% versus 5%, P < .001 ). Stroke severity and location did not differ. Old patients more often suffered from pneumonia (10.6% versus 2%, P < .003 ) and urinary tract infection (14.6% versus 2%, P = .001 ). Conclusions . Males dominate, and current smoking is more common in the young. Cervical artery dissection and nonarrhythmic heart disorders are frequent causes among young patients, while traditional risk factors dominate the old. Stroke severity is similar, but old patients seem more exposed for infectious complications.